Digital Transformation in Rural Areas: Improving Efficiency and Connectedness in Administrative Services in Batur Village, Semarang Regency - Dinullah Baihaqie, Ardhi (Riviera Publishing, 2024)
This study aims to investigate the impact of digital transformation on efficiency and connectivity in administrative services in Batur Village, Semarang Regency. Given the community's need for fast and effective public services, this study aims to explore how the application of information technology can improve village administration management. The method used is quantitative, with data collection through questionnaires distributed to 60 respondents consisting of villagers and village officials. This questionnaire includes demographic questions as well as questions related to the use of village administration services. The results of the analysis showed that 65% of respondents prefer online administration services, while 35% still rely on conventional methods. The average frequency of use of digital services by respondents reaches three times a month with a standard deviation of 1.1, indicating good consistency of use among the community. The validity test of the questionnaire confirmed that all questions were valid, with a significance value below 0.05. The reliability test using Cronbach's Alpha showed a value of 0.82, indicating high consistency in the results obtained. In addition, 80% of village officials involved in website management reported that the digital system had increased the efficiency of administrative management, accelerated the service process, and allowed them to focus on other development tasks. These findings indicate that people, especially those of productive age, are starting to adapt to digital-based administrative services, which not only facilitate access to information but also increase efficiency and transparency in public services. Thus, this study provides an important contribution to understanding the positive impact of digital transformation in improving the quality of administrative services in villages, as well as encouraging the use of technology in the public sector to respond to the evolving needs of society.